The Application of Guided Writing To Enhance Ability in Writing Procedure Texts of the Eleventh Grade Students at SMK Kosgoro 1 Sragen in 2016/ 2017 Academic Year - Widayat, Paramitha Fitriana, Drs. Djoko Srijono, M.Hum (2017)
Abstract This research aims at describing the application of guided writing to enhance ability in writing procedure texts of the eleventh grade students at smk kosgoro 1 sragen in 2016/ 2017 academic year. The objectives of the research are to describe the application of guided writing to enhance ability in writing procedure texts of the eleventh tkr 1 grade student at smk kosgoro 1 sragen in 2016/ 2017 academic year and the student's response. This research useas descriptive study. The subject of the research focuses on students of eleventh grade of SMK Kosgoro 1 Sragen. In collecting the data, the researcher uses observation, document analysis, and interview. The collected data are analyzed by collecting, reducing, and displaying data, classifying and verifying the data, and drawing conclusion. Based on the research finding, it was found that the application of guided writing related to the process of pre- writing, whlist- writing, and post- writing. The teacher used model paragraph, comprehension question, language based exercise, oral composition, and written composition type of guided writing. It was be done by the teacher in application guided writing. The student's response about application of guided writing is good attention, anthusiastically, braver, active, and funny. Teacher can also find the students whether active and understand or not. Keywords: guided writing, teaching writing